Performance of asphalt mixture incorporating recycled waste - Hamid N.B.; Abdullah M.E.; Sanik M.E.; Mokhtar M.; Kaamin M.; Raduan R.; Ramli M.Z. (American Institute of Physics Inc., 2023)
Nowadays, the amount of premix waste was increased every year, especially at the batching plants. Normally, the waste materials will be discarded without doing any innovative and effective research about those materials. This situation has become one of the global concerns due to the increasing number of premix waste produced every year. Therefore, the aim of this study is to evaluate the performance of hot mix asphalt (HMA) using premix waste on improving asphalt mixture fatigue behaviour. The method used in this study was Superpave mix design method. The sample conducted in this study were 0%, 10%, 20%, 30%, and 100% of premix waste respectively. For a binder test, the laboratory test conducted were penetration test, softening test and thin film oven test while for the performance test were resilient modulus test and indirect tensile fatigue test. From the laboratory test, the resilient modulus test was conducted with two different temperature which was 25C and 40C. The result from that test was 20% of premix waste had higher resilient modulus at that two different temperatures compared to another samples. From that test also shown that the sample at the lower temperature which was 25C has higher resilient modulus compared to the temperature of 40C. Indirect tensile fatigue test showed that the 30% of premix waste sample was suitable for the modified asphalt mixture with referring to the maximum deformation and strain for comparison control, 10%,20%, and 100% of premix waste samples. So, it can be concluded that premix waste inhibits great potential as road construction material and suitable for repeated traffic loading. 2017 Author(s).